Exchange rate management in a balance of payments crisis : the Guyana and Jamaica experience. - BENNETT, Karl M. (1992)
Argues that because of the unique characteristics of the balance of payments crisis in Guyana and Jamaica, the magnitude of the excess demand for foreign exchange at the prevailing exchange rate is an inappropriate guide to the extent of the devaluation required to correct currency overvaluation. Presents a case for a fixed exchange rate regime.